Overweight and obese children's psychosocial effects: A review of the literature - Farijah Ismail; D. Maryama Ag. Daud; Christina Peter Ligadu (Human Resource Management Academic Research Society, 2021)
Childhood obesity has reached epidemic proportions in both developed and developing nations. Childhood obesity and overweight have been shown to have a negative influence on both physical and psychological health. The goal of this study was to look at the psychological and psychosocial effects of childhood obesity. Obese and overweight children were more likely than their healthy-weight peers to have various related psychosocial issues, which may be affected negatively by childhood obesity stigma, taunting, and bullying. Childhood obesity stigma, taunting, and bullying are widespread and can have significant implications for mental and physical health and performance. Furthermore, childhood obesity can have a significant impact on a child's psychological and emotional well-being, self-esteem, and overall quality of life. To battle the present obesity epidemic, a coherent and comprehensive strategy is required to counteract this rising trend that jeopardises the health and well-being of the next generation.